Tumor Necrosis Factor Inhibitors Reduce Spinal Radiographic Progression in Patients With Radiographic Axial Spondyloarthritis: A Longitudinal Analysis From the Alberta Prospective Cohort - Alexandre Sepriano (2022)
Objective: To investigate whether tumor necrosis factor inhibitors (TNFi) impact spinal radiographic progression in patients with axial spondyloarthritis (SpA) and whether this is coupled to their effect on inflammation. Methods: Patients with axial SpA fulfilling the modified New York criteria were included in a prospective cohort (the ALBERTA Follow Up Research Cohort in Ankylosing Spondylitis Treatment). Spine radiographs, performed every 2 years for up to 10 years, were scored by 2 central readers, using the modified Stoke Ankylosing Spondylitis Spine Score (mSASSS). The indirect effect of TNFi on mSASSS was evaluated with generalized estimating equations by testing the interaction between TNFi and Ankylosing Spondylitis Disease Activity Score (ASDAS) at the start of each 2-year interval (t). If significant, the association between ASDAS at t and mSASSS at the end of the interval (t+1) was assessed in 1) patients treated with TNFi at all visits, 2) patients treated with TNFi at some visits, and 3) patients who were never treated with TNFi. In addition, the association between TNFi at t and mSASSS at t+1 (adjusting for ASDAS at t) was also tested (direct effect). Results: In total, 314 patients were included. A gradient was seen for the effect of ASDAS at t on mSASSS at t+1 (interaction P = 0.10), with a higher progression in patients never treated with TNFi (β = 0.41 [95% confidence interval (95% CI) 0.13, 0.68]) compared to those continuously treated (β = 0.16 [95% CI 0.00, 0.31]) (indirect effect). However, TNFi also directly slowed progression, as treated patients had on average an mSASSS 0.85 units lower at t+1 compared to untreated patients (β = −0.85 [95% CI −1.35, −0.35]). Conclusion: Our findings indicate that TNFi reduce spinal radiographic progression in patients with radiographic axial SpA, which might be partially uncoupled from their effects on inflammation as measured by the ASDAS.